Pengaruh Kecerdasan Emosional, Intelektual, Spiritual, Love Of Money Pada Sikap Mahasiswa Mengenai Etika Profesi Akuntan - Pratama, Ida Bagus Putu Weda; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
The purpose of this study was to obtain empirical evidence of the influence of emotional intelligence, intellectual intelligence, spiritual intelligence and love of money on student attitudes regarding professional ethics of accountants. The research approach used in this study is a quantitative approach using primary data. The sampling technique used is nonprobability sampling with purposive sampling method. The number of samples used in this study were 107 samples. The analysis technique used is multiple linear regression. The results of this study indicate that emotional intelligence, intellectual intelligence and spiritual intelligence have a positive effect on student attitudes regarding professional ethics of accountants while love of money has a negative effect on student attitudes regarding professional ethics of accountants. Practical implications for students that they must prepare for their ethical attitude before entering the workforce. Keywords: Emotional intelligence, intellectual intelligence, spiritual intelligence, love of money, student attitudes regarding professional ethics of accountants.